Family Counseling Strategies to Increase Generation Z Parental Involvement in Early Childhood Education - Dwi Noviana Komsi (Bulletin of Early Childhood, 2025)
This study aims to analyze technology-based family counseling strategies to increase the involvement of Generation Z parents in early childhood education. Generation Z, known as digital-natives, exhibits distinctive engagement patterns, relying on educational apps, online communication groups, and social media to monitor children's development, but faces challenges such as time management, digital fatigue, and misalignment of home parenting styles with school expectations. The research method used a descriptive qualitative approach through in-depth interviews, observation, and documentation with 20 Gen Z parents at the Lubuk Linggau Early Childhood Education (PAUD) institution. Data were analyzed using the Miles and Huberman interactive model, including reduction, presentation, and conclusion drawing. The results showed that family counseling strategies that integrate technology, time management training, and collaborative parent-teacher forums significantly increased parents' awareness, confidence, and skills in supporting children's learning, both at home and at school. This counseling is in line with Bowen's family systems theory which emphasizes the impact of behavioral changes on overall family dynamics, and Baumrind's democratic parenting theory which is in line with the values of freedom and dialogue held by Gen Z parents. These findings strengthen previous research on parental involvement, while offering a novelty in the form of an adaptive family counseling model that suits Generation Z's digital communication style. The implications of this research emphasize the importance of developing flexible, interactive, and technology-based family counseling programs to encourage ongoing parental involvement to support optimal early childhood development.